2022
DOI: 10.1037/abn0000735
|View full text |Cite
|
Sign up to set email alerts
|

Pedophilia is a taxon among 706 adult males assessed at a civil commitment center.

Abstract: This study examined whether pedophilia is best understood as a dimension or a discrete class (taxon). We considered pedophilia to include both physical sexual attraction to children as well as emotional attraction to children and childhood. Archival data from 901 adult males from a U.S. civil commitment treatment center for sexually dangerous persons were used. Three indicators were submitted to Meehl and Ruscio's taxometric analyses: (a) a screening scale for pedophilic interests based on criminal history, (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…Individuals were identified as having a clinically significant problem on items from the STABLE-2007 (defined as scores of 1 or 2) and on the SSPI (defined as a score of 3 or more; Brankley, 2019 ) in an average risk community sample ( Table 4 ). A majority of individuals within Level IV presented with general antisocial tendencies (e.g., lack of concern for others and poor cognitive problem solving).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals were identified as having a clinically significant problem on items from the STABLE-2007 (defined as scores of 1 or 2) and on the SSPI (defined as a score of 3 or more; Brankley, 2019 ) in an average risk community sample ( Table 4 ). A majority of individuals within Level IV presented with general antisocial tendencies (e.g., lack of concern for others and poor cognitive problem solving).…”
Section: Resultsmentioning
confidence: 99%
“…The SSPI was computed from existing variables within the average risk community sample dataset as part of a separate study of the SSPI’s construct and predictive validity (see Helmus et al., 2015 ). We calculated the percent of individuals scoring 3 or higher based on findings that these scores represent a clinically relevant cut-score for the diagnosis of pedophilia ( Brankley, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…For each offender, an overall Z-score pedophilic deviance index was computed, indicating the difference in Z scores between the highest response to deviant pedophilic stimuli minus the highest response to non-deviant stimuli. Consistent with evidence that pedophilic sexual preference is distributed as a distinct taxonic (Brankley et al, 2022;McPhail et al, 2018;Schmidt et al, 2013) and in accord with prior cutoffs (Seto, Sandler, et al, 2015;Seto, Stephens, et al, 2015), we used a cutoff of Z = 0.25 (indicating a 0.25 SD higher response for deviant stimuli compared to non-deviant stimuli) to determine the presence of pedophilic preferences as measured by PPG.…”
Section: Phallometric Assessmentmentioning
confidence: 95%
“…The studies have all used taxometric analyses, which provide a set of non-overlapping procedures that allow for empirical examination of latent structure in psychological constructs (Ruscio et al, 2006). Interestingly, these studies have found rather divergent results, with studies providing evidence for dichotomous (i.e., two taxa; Brankley, Knight, & Hanson, 2022;Schmidt et al, 2013), dimensional (Stephens et al, 2017), trichotomous (i.e., three taxa;, and ambiguous latent structure (Mackaronis, Byrne, Strassberg, Marcus, & Solari, 2011; see Table 1 for an overview of these studies). At present, the while most studies suggest categorical structure, studies with larger samples suggest dimensional structure.…”
Section: Introductionmentioning
confidence: 99%
“…Their sample consisted of men with sexual offence histories, which may have limited the number of members of a putative complement class (i.e., those who will show no sexual interest in children). The study by Brankley et al (2022) contains similar methodological limitations, with the added limitations of exclusively relying on observer-rated measures instead of examining participant-generated data and using a novel conceptualization of these sexual interests. relied upon a single measurement modality (i.e., penile plethysmography), raising questions of construct coverage.…”
Section: Introductionmentioning
confidence: 99%